Take Control of Your Online Privacy, 4th Edition - Kissell, Joe (Take Control Books, 2019)
Nowadays, it can be difficult to complete ordinary activities without placing your personal data online, but having your data online puts you at risk for theft, embarrassment, and all manner of trouble. In this book, Joe Kissell helps you to develop a sensible online privacy strategy, customized for your needs . Whether you have a Mac or PC, iOS or Android device, set-top box, or some other network-enabled gadget, you'll find practical advice that ordinary people need to handle common privacy needs (secret agents should look elsewhere). You'll learn how to enhance the privacy of your internet connection, web browsing, email messages, online chatting, social media interactions, and file sharing, as well as your mobile phone or tablet, and Internet of Things devices like webcams and thermostats. Parents will find important reminders about protecting a child's privacy. The book also includes Joe's carefully researched VPN recommendations. The book is packed with sidebars that help you get a handle on current topics in online privacy , including international travel, quantum computing, why you should beware of VPN reviews online, two-factor authentication, privacy and your ISP, understanding how ads can track you, and more. You'll receive savvy advice about topics such as these: Why worry? Learn who wants your private data, and why they want it. Even if you don't believe you have anything to hide, you almost certainly do, in the right context. Would you give just anyone your financial records or medical history? Didn't think so. Set your privacy meter: Develop your own personal privacy rules-everyone has different privacy buttons, and it's important to figure out which matter to you. Manage your Internet connection: Understand privacy risks, prevent snoops by securing your Wi-Fi network, and take key precautions to keep your data from leaking out. Also find advice on using a VPN, plus why you should never believe a VPN review that you read on the Internet-even if it seems like it was written by Joe! Browse and search the web: Learn what is revealed about you when you use the web. Avoid bogus websites, connect securely where possible, control your cookies and history, block ads, browse and search anonymously, and find out who is tracking you. Also, take steps to protect passwords and credit card data. Send and receive email: Find out how your email could be intercepted, consider when you want email to be extra private (such as when communicating wi...